Additive Fertigung mit Kunststoffen: Potenziale, Entwicklungen und Trends - Drummer, Dietmar; Wudy, Katrin (Spritzgießen 2018, 2018)
"Additive manufacturing processes with plastics are on the threshold of revolutionizing the manufacturing environment" or “Additive manufacturing techniques are developing from rapid prototyping to serial production” – such or similar statements can be found in commercial and scientific publications in the field of additive technologies. What is the state of the art in additive technologies? Where are the challenges and strength of additive techniques? Which trends can be observed in this highly dynamic environment and which topics are dedicated to the university environment? These are the questions that the present publication is pointing out.
CRIS-Team Scopus Importer:2023-03-29